A school of public health responds to the pandemic: A case study from Washington D.C. - Hyder, Adnan A.; Thorpe, Jane H.; Migliaccio, Eugene; Kazeem, Natasha; Goldman, Lynn R. (Frontiers in Public Health, 2022)
The emergence of COVID-19 immediately affected higher education, and the closure of campuses at the start of the pandemic in March of 2020 forced educational institutions to quickly adapt to changing circumstances. Schools of public health faced challenges not only of shifting to remote learning and work environments, but also uniquely redirecting public health research and service efforts toward COVID-19. This paper offers a case study of how the Milken Institute School of Public Health at the George Washington University (GWSPH), the only school of public health in the nation's capital, initially adapted to the COVID-19 pandemic. Using a modified version of the Public Health Preparedness and Response Core Competency Model created by the Association of Schools and Programs of Public Health and the Centers for Disease Control and Prevention, we analyze how GWSPH worked in three areas—research, education, service/operations. We reviewed this initial response across four domains: model leadership; communication and management of information; planning and improving practice; and protecting worker (and student) health and safety. The adaptation of the model and the analysis of GWSPH's initial response to the pandemic can be useful to other schools of public health and health sciences in the United States and beyond, in preparing for all hazards. We hope that such analysis also informs the current concerns of schools such as return to in-person education as well as planning for future public health crises.